AGRESIVITAS PAJAK SEKTOR PERTAMBANGAN INDONESIA - Arifin, Mohammad Aryo (Jurnal Keuangan dan Bisnis, 2020)
This study aims to determine the factors which influenced the tax aggressiveness. Liquidity, Leverage, Profitability, Capital Intensity, and Inventory Intensity are the independence variable that be used in this research. This research use statistical Eviews. The result shows the factors affect the tax aggressiveness significantly are Leverage. Furthermore, Liquidity, Profitability, Capital Intensity and Inventory Intensity have not significant influence toward tax aggressiveness.